Da‘wa – obowiązek religijny czy narzędzie w rękach fundamentalistów? Misyjne radykalne ugrupowania muzułmańskie - Jędrzejczyk-Kuliniak, Katarzyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Contemporary fundamentalist movements have been shaped be exposure to confrontation with modernity, and globalization. The causes of fundamentalism arising are varied, but it can be brought to a conflict between politicized Islam and the Western world with its values. The idea promoted by Muslim fundamentalists in Europe is the need of implementation of the religious principles into the political sphere of European countries. Some of these movements seek to create a caliphate, like it was in the early age of Islam. Not all the movements proclaim the need to change the political order, the legal system, some want to change only the social order. These kind of movement, are called traditional. The condition necessary for the realization of the ultraorthodox Islamic ideas is to gain as many followers as possible, through the spread of the Quran and the Sunnah (da‘wah). The paper presents the concept of politicized Islam and the aspects of religious missionary activity of Muslim fundamentalists, at the example of the Muslim Brotherhood. The study is focused on the Sunni fundamentalism.
Keywords: Europe; fundamentalism; Islam; missionary; politics